1992
DOI: 10.1002/lipi.19920940909
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Separating Polar Lipids from Oat Oil

Abstract: Byl? F o r s s e l l , R. K e r v i n e n , M . A I k i o a n d K . P o u t a n e n *Polar lipids of crude oat oil were investigated. Oat oil was separated from oats by extraction with isopropanol. Polar Iipids were fractionated from crude oil by supercritical CO2-extraction, by ultrafiltration in hexane and by water degumming. The polar fraction from C02-extraction had the highest phospholipid and lowest tocopherol content. The polar fractions made by different methods possessed similar antioxidative properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Crude soya lecithin was kindly donated by Mildola (Kantvik, Finland). Oat oil was extracted from oats (cv Veli) using propan-2-ol as the solvent (Forssell et al 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude soya lecithin was kindly donated by Mildola (Kantvik, Finland). Oat oil was extracted from oats (cv Veli) using propan-2-ol as the solvent (Forssell et al 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Oil was removed from crude soya lecithin by washing several times with acetone at ]5¡C. The non-polar lipids from oat oil were removed by extraction with supercritical (Forssell et al 1992). The total phos-CO 2 pholipid contents of the oil-free soya and oat lecithins based on analysis of the phosphorus content were about 90% and 40%, the remainder being most probably glycolipids.…”
Section: Ecithins and Their Hydrolysis Productsmentioning
confidence: 99%
“…Oat sterols have also been reported to have antioxidative properties (White andArmstrong 1986, Kahlon 1989). Forssell et al (1992) reported that oat lecithin is a better antioxidant than soy or turnip rape lecithin. Emmons et al (1999) found that the total phenolic content of oat was significantly correlated with antioxidant activity, measured by β-carotene bleaching.…”
Section: Total Antioxidant Activitymentioning
confidence: 99%
“…Sample (10-20 mg) was dissolved in a mixture of 0.6 mL chloroform-d 1 and 0.3 mL methanol-d 4 and transferred to an NMR tube (5 mm o.d. ).…”
Section: Methodsmentioning
confidence: 99%
“…Oat oil and fractions thereof have interesting physical, nutritional, and dermatological properties, and can find many uses in the food, cosmetics, and pharmaceutical industries (4)(5)(6).…”
mentioning
confidence: 99%